Analisis Sistem Informasi Kesehatan Daerah (SIKDA) Generik Di Unit Rekam Medis Puskesmas Langsat Tahun 2020 - Welly Sando; Dedi Dedem; Suci Badri Yana (LPPM Universitas Muhammadiyah Riau, 2020)
Regional information system is a term that is used to describe a system consisting of a combination of input such as human resources (brainware), software, information needs format (informware), information technology and communication technology, the process of sending an analysis report recording (entry). the feedback and output data information mechanism that can be accessed together and has adequate quality, regional information system in the Langsat Health Center Medical Record Unit only started in 2017, SIKDA in the medical records unit lacks Human Resources because it does not there is a Medical Record and IT graduate. Obstacles that occur, such as disruption of soft ware and hard ware networks when opened, experience delays, causing delays in the given services. For the Fund itself, there is no special budget provided for the implementation of theregional information system application because it has been allocated by the Health Office. Budget allocation of funds is held only if needed. This type of qualitative research uses interview and observational sheets. The research was conducted in February-September, at Langsat Public Health Center, Pekanbaru City. The research subjects were the Head of Langsat Community Health Center, the Head of the Medical Records Unit, the person in charge of SIKDA, and Operators. Data analysis was used by systematically managing the interview guidelines, then processing the data, data from observations were identified to describe each variable, a summary will be presented in a narrative form. The results of this study indicate that the Generic regional information system in the Medical Records Unit has been running at its maximum, even though there is a lack of calm in Human Resources there are no medical records and IT graduates. Infrastructure is lacking in terms of ginset, Fund Allocation is not a special budget. Must improve Human Resources, Facilities and Infrastructure.